Pengembangan Kawasan Stasiun Tugu dengan Penekanan Wayfinding di Yogyakarta - Yunisa Zahrah; Kusumaningdyah Nurul Handayani; Ummul Mustaqimah (ARSITEKTURA, 2021)
The proposal aims to bring an accessible, time efficient, and secure design of Tugu Train Station in Yogyakarta City. Yogyakarta happens to be located strategically on the main routes of Java. It is one of the reasons why the city becomes a tourist destination, both domestic and international. Tugu Train Station manages to reach passengers number increase by 10-17% annually. The train station has a good prospect to be developed into a multifunctional train station. The design proposal rises some problems: designing exterior spaces which directs users to the site, interior spaces which makes users navigate easily, and a seamless, time efficient, and clear movement flow from the site to the building. The implementation of wayfinding method is based on post-occupancy evaluation of the existing compound in which confusing building layout creates difficulties in mobility for the passengers. Wayfinding method focuses on spatial organisation, movement flow organisation, and signage placement. This design proposal would expand existing train station buildings to provide more rooms in the anticipation of passenger increase for year to come; as well as to build new public facilities. Furthermore, the implementation of wayfinding method is expected to create an accessible, time efficient, and secure layout which in turn caters various types of passenger.